Cosmic mind, universal algorithm, and efforts to build a prosperous life in the age of nanotechnology : (hindu cosmological perspective) - Ida Bagus Wika Krishna; Krishna S. Yogisvari; Ni Putu Pita Sari (Life and Death: Journal of Eschatology, 2023)
Hindu cosmology is the knowledge of the ins and outs of the universe. One topic concerns the cosmic mind and human existence on Earth. Vedic cosmology teaches that the universe has a cosmic mind and energy that builds up a large and expansive natural energy field. This energy field is often referred to as Indrajala or Indra's net. Humans and all entities are firmly connected in this net of Indra. Humans living on Earth radiate energy from their bodies and minds to the universe. The universe will accept the radiation of these thoughts and feelings. Later, the term universe algorithm emerged, which is a term that shows how the universe as a system is structured and organized. This is in line with the cosmic mind in the Vedas. The universe is likened to a sophisticated and complete computer with the laws of order in it. The universe's algorithms can easily read the signals of the human mind and provide appropriate feedback. Thus, humans determine their destiny is correct and reasonable. Because the power of the human mind is mighty and connected to the cosmic mind, this article results from literature research based on Hindu cosmology which discusses the cosmic mind, universe algorithms, and efforts to build a prosperous life. The data is obtained by reading the text using the theory of Vedic Interpretation. Data were analyzed using content analysis. The findings of this study are that the theory of the cosmic mind, the energy field known as the senses, can be studied through the phenomena of the universe's algorithm and is strongly connected with the human mind. This theory is relevant with the purpose of life on Earth, jagadhita, and continues its evolution in higher stages. As extraordinary beings, humans can do many things and build a good life, leading to awareness and enlightenment. Vedic cosmology helps to understand the laws of the universe and the cosmic energy flows that drive evolution.